Respuesta :
Answer:
p(-5)=-11,987
p(3)=-227
Step-by-step explanation:
To find the value of the function p(-5) just substitute x=-5 into the function expression instead of x:
[tex]p(-5)=2\cdot (-5)^5-9\cdot (-5)^4-2\cdot (-5)^2+12\cdot (-5)-2=\\ \\=-6,250-5,625-50-60-2=-11,987[/tex]
To find the value of the function p(3) just substitute x=3 into the function expression instead of x:
[tex]p(3)=2\cdot 3^5-9\cdot 3^4-2\cdot 3^2+12\cdot 3-2=\\ \\=486-729-18+36-2=-227[/tex]
Answer with Step-by-step explanation:
We are given a function:
[tex]p(x) = 2x^5-9x^4-2x^2+12x-2[/tex]
We have to find the value of p(-5) and p(3)
[tex]p(-5) = 2\times (-5)^5-9\times (-5)^4-2\times (-5)^2+12\times (-5)-2\\\\=-6250-5625-50-60-2\\\\=-11987[/tex]
[tex]p(3) = 2\times 3^5-9\times 3^4-2\times 3^2+12\times 3-2\\\\=486-729-18+36-2\\\\=-227[/tex]
Hence, p(-5)= -11987
and p(3)= -227